Recognition of Invasive Prostate Cancer Using a GHRL Polypeptide Probe Targeting GHSR in a Mouse Model In Vivo - Ye, Huamao; Yang, Yue; Chen, Rui; Shi, Xiaolei; Fang, Yu; Yang, Jun; Dong, Yuanzhen; Chen, Lili; Xia, Jianghua; Wang, Chao; Yang, Chenghua; Feng, Jun; et al. (Current Pharmaceutical Design, 2020)
Background: Ghrelin (GHRL) is a polypeptide that can specifically bind to the growth hormone secretagogue receptor (GHSR). The expression of GHSR is significantly different in normal and prostate cancer (PC) tissues in humans. It is important to find an effective diagnostic method for the diagnosis and prognosis of invasive PC/neuroendocrine prostate cancer (NEPC). Methods: GHRL and GHSR mRNA levels were determined by a quantitative real-time polymerase chain reaction in PC tissues. The expression of GHRL and GHSR proteins was assessed by Western blot assay and immunohistochemistry. A GHRL polypeptide probe was synthesized by standard solid-phase polypeptide synthesis, and labeled with Alexa Fluor 660. Confocal microscopy was used to capture fluorescence images. Living imaging analysis showed tumor areas of different invasiveness in mice models. Results: The levels of GHRL and GHSR copy number amplification and mRNA expression were increased in invasive PC/NEPC, and the protein expression levels of GHRL and GHSR were similarly increased in NEPC. The GHRL polypeptide probe could effectively bind to GHSR. In PC3 cells, it was found that the GHRL probe specifically binds to GHSR on the cell membrane and accumulates in the cells through internalization after binding. Live imaging in mice models showed that there were different signal intensities in tumor areas with different invasiveness. Conclusion: GHSR and GHRL might be used in molecular imaging diagnosis for invasive PC/NEPC in the future.
Keywords: Prostate cancer